2019
DOI: 10.3390/cells8101295
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cells Develop Defined Cellular Phenotypes After 3D-Bioprinting in Different Bioinks

Abstract: Malignant melanoma is often used as a model tumor for the establishment of novel therapies. It is known that two-dimensional (2D) culture methods are not sufficient to elucidate the various processes during cancer development and progression. Therefore, it is of major interest to establish defined biofabricated three-dimensional (3D) models, which help to decipher complex cellular interactions. To get an impression of their printability and subsequent behavior, we printed fluorescently labeled melanoma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 63 publications
(68 reference statements)
1
31
0
Order By: Relevance
“…In addition, according to the supplier’s protocols, samples were incubated for characterization and cell culture in fluid media containing calcium to ensure prolonged stability in a watery environment. In accordance with our results, the recently published paper by Schmidt et al qualitatively tested the stability of 3D-printed structures based on a similar alginate and nanocellulose-based bioink, without laminin [ 44 ]. The authors showed that 3D-printed structures starting from this bioink did not show any macroscopically visible changes, suggesting stability of the printed structures up to 14 days and the absence of significant swelling, as demonstrated by the lack of a clear increase in scaffold volume.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, according to the supplier’s protocols, samples were incubated for characterization and cell culture in fluid media containing calcium to ensure prolonged stability in a watery environment. In accordance with our results, the recently published paper by Schmidt et al qualitatively tested the stability of 3D-printed structures based on a similar alginate and nanocellulose-based bioink, without laminin [ 44 ]. The authors showed that 3D-printed structures starting from this bioink did not show any macroscopically visible changes, suggesting stability of the printed structures up to 14 days and the absence of significant swelling, as demonstrated by the lack of a clear increase in scaffold volume.…”
Section: Discussionsupporting
confidence: 90%
“…According to our results, Novikova et al reported that MSCs from bone marrow cultured in an alginate hydrogel appeared as atypical cells with spherical shape and inhibited metabolic activity [ 53 ]. Other studies reported that NFC/A hydrogels do not allow or inhibit proliferation and growth of several different types of cells [ 35 , 44 ]. For instance, Müller et al also reported a significant decrease in cell proliferation of chondrocytes embedded in an NFC/A hydrogel [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A laminin-enriched crosslinkable biomixture provided by Cellink company was used as a bioink. Based on previous studies, laminin-enriched bioink was selected to support the maintenance of hepatic profile expression and clonal expansion of encapsulated cells that have the ability to migrate within bioprinted structures after bioprinting [24,25]. Initially, encapsulated HepG2 cells were well distributed based on the movement of the bioprinter nozzle.…”
Section: Fabrication Of 3d Bioprinted Human Liver Tissuementioning
confidence: 99%
“…Additional components, such as laminin/peptide additives to Matrigel (Schmidt et al 2019), as well as infiltrating cell types, such as fibroblasts (Amann et al 2014), have been incorporated into semisolid matrices to interact with tumor cells in a way that mimics the in vivo biology of the tumor. These approaches have been used to create ex vivo niches that resemble tumor microenvironments.…”
Section: Three-dimensional Bioprinted Models and Organotypic Culturesmentioning
confidence: 99%